GAIN DETERMINATION OF HOMOGENEOUS LADDER CIRCUITS - V. S. Safarian; L. V. Safarian (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2005)
The paper contains relationships determining input resistances and gains from any i-x terminal pairs of a homogeneous ladder circuit. These relationships are expressed in parameters of one four-terminal network.